The effect of environmental factors on preweaning survival rate of Borana and Arsi-Bale kids - Hailu, D.; Mieso, Guru; Alemayehu, N.; Dawo, F.; Duguma, G. (Elsevier, 2006)
The effect of environmental factors on preweaning survival rate of Arsi-Bale and Borana kids at the Adami Tulu Agricultural Research Center, was investigated. Data collected on 702 kids born between 1999 and 2003 were used to evaluate the effect of year, parity, breed type, sex, season of birth, litter size and birth weight on survival rate of the goats. All the environmental factors significantly influenced the survival rate of kids. The overall preweaning survival rate of kids averaged 69%. Survival of the Arsi-Bale kids was 75% while it was 57% for the Borana kids. Survival of single (70%) and twin (70%) born kids were high compared to survival rate of triplets (43%). Kids born during the wet season had better survivability than kids born in the other seasons. Kidding occurring in the early dry season (September-November) had the highest mortality rate of 42%. A maximum survival rate was found from kids with 3.1-4.5 kg of live weight at birth. The study indicated that by instituting adequate management improvement actions in addition to selection for larger kids at birth and at weaning, the productivity of goats could be improved.